(EVERY)BODYHOME? A PHENOMENOLOGICAL PERSPECTIVE ON THE EXPERIENCE OF INCARCERATED EXISTENCE IN THE CONTEMPORARY SOUTH AFRICAN SOCIETY - Veldsman, Daniël Petrus (Scriptura, 2007)
based on a detailed analysis and critical discussion of Leder's book The absent body in which he disentangles in an insightful phenomenological manner the Cartesian dualistic heratige, this article forces on the experience of incarcerated existence within contemporary crime- ridden South African society, which is characterised as the 'disillusionment' pof exploited, forgotten and manipulated bodies. In contrast to Leder's proposal of Neo-Confucianism, the author proposes and explores the African concept of the body of Christ for the"dys-illusioned" South African society in which the social fabric has been destroyed and human dignity must be restored in order for every(body) to be at home.